Preoperative systemic inflammatory biomarkers can improve recurrence prediction of non-muscle invasive bladder cancer after endoscopic resection – a prospective observational study - Bardowska, Klaudia; Krajewski, Wojciech; Kołodziej, Anna; Kościelska-Kasprzak, Katarzyna; Bartoszek, Dorota; Żabińska, Marcelina; Chorbińska, Joanna; Królicki, Tomasz; Krajewska, Magdalena; Szydełko, Tomasz; Kamińska, Dorota (Contemporary oncology (Poznan, Poland), 2025)
Non-muscle invasive bladder cancer (NMIBC) is one of the most commonly diagnosed urogenital types of cancer with a relatively favourable prognosis. Cystoscopy stands as the most significant diagnostic and monitoring procedure, however more accessible methods are needed for diagnosis and follow-up. A total of 285 pa-- tients with NMIBC were enrolled in this prospective study. Complete blood count (CBC) biomarkers and nutritional risk scores were evaluated for predicting cancer recurrence or progression after radical transurethral resection of bladder tumour (TURB). Additionally, the correlation between CBC biomarkers and European Organisation for Research and Treatment of Cancer (EORTC) risk scores was performed. A final study group with complete follow-up and dataset, comprised of 183. After a 3-month follow-up period, 104 subjects experienced cancer recurrence or progression. A group of 79 patients were tumour free. The neutrophil-to-lymphocyte ratio (NLR) showed the highest area under the curve of 0.618 (95% CI: 0.536-0.699) with = 0.0047, for discrimination of the study outcomes. None of nutritional risk scores has predicted disease progression or recurrence. Neutrophil-to-lymphocyte ratio, monocyte-to-lymphocyte ratio and derived NLR enhanced the diagnostic performance for EORTC recurrence and progression points. Complete blood count biomarkers can predict recurrence or progression of NMIBC after TURB, yet nutritional risk scores have demonstrated inadequate predictive value. Complete blood count biomarkers increase prognostic properties of EORTC risk score.